Inguinal Hernia. Causes, Symptoms and Treatment of Inguin Hernia (Eurasian Research Bulletin, 2022)
The aim of the study was to systematize and evaluate the causes of inguinal hernias and, on this basis, to choose the optimal method of treatment.